From benign adrenal incidentaloma to adrenocortical carcinoma: an exceptional random event. Issue 6 (June 2017) - Belmihoub, I; Silvera, S; Sibony, M; Dousset, B; Legmann, P; Bertagna, X; Bertherat, J; Assié, G
Abstract : New European guidelines for the management of adrenal incidentalomas were recently released. One of the most novel recommendations is to stop following patients when they present a typical, small and non-secreting adenoma. We report here the case of a 71-year-old man with such an adenoma, who developed an adrenocortical carcinoma (ACC) fourteen years later, with subsequent metastases and death. Clinically, he had a normal blood pressure and no sign of hormonal hypersecretion. The hormonal work-up showed no hormone excess: urinary free cortisol level was normal, the diurnal cortisol rhythm was respected and urinary catecholamine metabolites levels were normal. Computed tomography (CT) scan showed a homogeneous lesion, with a low density. The lesion remained unchanged during the five years of follow-up. Eight years after the last CT, a large right heterogeneous adrenal mass was incidentally discovered during an ultrasound examination. On CT scan, it was a 6 cm heterogeneous tumor. On hormonal work-up, there was no secretion. The patient was operated of an adrenalectomy, and the histology described an ACC with a Weiss score at 8, with no benign contingent. To our knowledge, this is the first case of an ACC occurring in a patient with prior adrenal imaging showing a typical benign adenoma.